Longitudinal Dynamics of Circulating Tumor Cells and Circulating Tumor DNA for Treatment Monitoring in Metastatic Breast Cancer. (2021) - Gerratana, Lorenzo; Davis, Andrew A.; Zhang, Qiang; Basile, Debora; Rossi, Giovanna; Strickland, Kimberly; Franzoni, Alessandra; Allegri, Lorenzo; Mu, Zhaomei; Zhang, Youbin; Flaum, Lisa E.; Damante, Giuseppe; et al.
Abstract : PURPOSE: Liquid biopsy–based biomarkers, including circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA), are increasingly important for the characterization of metastatic breast cancer (MBC). The aim of the study was to explore CTCs and ctDNA dynamics to better understand their potentially complementary role in describing MBC. METHODS: The study retrospectively analyzed 107 patients with MBC characterized with paired CTCs and ctDNA assessments and a second prospective cohort, which enrolled 48 patients with MBC. CTCs were immunomagnetically isolated and ctDNA was quantified and then characterized through next-generation sequencing in the retrospective cohort and droplet digital polymerase chain reaction in the prospective cohort. Matched pairs variations at baseline, at evaluation one (EV1), and at progression were tested through the Wilcoxon test. The prognostic role of ctDNA parameters was also investigated. RESULTS: Mutant allele frequency (MAF) had a significant decrease between baseline and EV1 and a significant increase between EV1 and progression. Number of detected alterations steadily increased across timepoints, CTCs enumeration (nCTCs) significantly increased only between EV1 and progression. MAF dynamics across the main altered genes was then investigated. Plasma DNA yield did not vary across timepoints both in the retrospective cohort and in the prospective cohort, while the short fragments fraction showed a potential role as a prognostic biomarker. CONCLUSION: nCTCs and ctDNA provide complementary information about prognosis and treatment benefit. Although nCTCs appeared to assess tumor biology rather than tumor burden, MAF may be a promising biomarker for the dynamic assessment of treatment response and resistance.